Swelling of cellulosic porous materials - mathematical description and verification - Geffert, Anton; Vacek, Ondrej; Jankech, Andrej; Geffertová, Jarmila; Milichovský, Miloslav (My University, 2017)
The swelling of natural porous materials, including bleached pulp, as represented by mathematical descriptions, is influenced by a variety of different operating factors. The formerly used Generalised Hygroscopicity Model leads to either a disproportion between a model and a limit value of the sorption capacity or to noticeable deviation in the early swelling phase. Alternatively, the so-called Simple Bounded Growth model solely depends on the maximum sorption capacity, ignoring the physical properties that affect the fibre swelling rate. This research shows that the combination of the two models best describes the swelling process of bleached pulp – a rapid swelling phase and a slower swelling phase. The combined model was found to be useful in characterizing the well-known hornification process.
Bobtnání celulózových porézních materiálů - matematický popis a verifikace
Keywords: Porous materials; Simple bounded growth model; Generalized hygroscopicity model; pórovité materiály; matematické modely bobtání; matematické modely navlhání